Which incision is better for living-donor right hepatectomy? Midline, j-shaped, or mercedes - DEMİRBAŞ, BAHA TOLGA (My University, 2013)
Incision-related morbidity for donors is a major concern in living-donor right hepatectomy (LDRH). Open approaches use midline, J-shaped, and Mercedes incisions for LDRH. We retrospectively studied 95 consecutive donors who underwent LDRH between January 2009 and November 2010. They underwent midline (n = 32), J-shaped (n = 28), or Mercedes (n = 35) incisions. We studied resection times, perioperative bleeding, postoperative hospital stay, and postoperative pain assessed by the visual analog scale (VAS) and by analgesic requirements as well as laboratory data and complications. Postoperative analgesic requirements and postoperative VAS scores were significantly lower in the midline group (P < .05) upon univariate but not multivariate analyses. The postoperative complications as well as other parameters were similar between the groups. In conclusion, compared with a J-type shaped or not for Mercedes incision, a donor hepatectomy can be satisfactorily performed via a midline incision by experienced surgeons without increased risk.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Yaşam Bilimleri; Temel Bilimler; Medicine; Health Sciences; Surgery Medicine Sciences; Life Sciences; Natural Sciences; İmmünoloji; Yaşam Bilimleri (LIFE); CERRAHİ; Klinik Tıp; Klinik Tıp (MED); TRANSPLANTASYON; IMMUNOLOGY; Life Sciences (LIFE); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); TRANSPLANTATION; General Immunology and Microbiology; Immunology; Surgery; Transplantation